The effect of vitamin C and Anacardium occidentale in two biochemical parameters of sportsmen in samarra city - Mowafak M. Zaidan; Hala H.M. jassim (Tikrit Journal of Pure Science)
This study was designed to investigate effects of the Vitamin C and cashew on biochemical parameters that include concentrations of Uric acid and Creatine phosphokinase, (60) sample of blood have collected  and they have divided for 4 groups (2 Control Group C1 ,C2 No treated)